Development Of A Big Book To Improve Literacy Skills Based On The Pancasila Student Profile - Gafur, Abd; Nuzulia, Nuril; Ghaffar, Abdul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The newest component of the independent curriculum is the Pancasila student profile. In terms of character education and increasing student competence, the Pancasila student profile is a reference for educational policy guidelines. One of the problems with literacy skills at Al-Muawanah Islamic Elementary School in Surabaya is that the majority of grade 1 students' literacy skills are still below standard. Some children still have difficulty distinguishing letters; when reading, there are words that are missing or even incomplete, and students' understanding of reading material is also below standard. Research and development use a model adapted by Borg and Gall. Of the ten development steps, researchers only implemented seven. The results of this development show: 1) The module specifications consist of a cover, introductory remarks, table of contents, materials, evaluation questions, and author biodata. The results of the research were 90.6% content experts with good qualifications, 89.3% learning media experts with good qualifications, and 94.6% learning experts with good qualifications. 2) To determine the attractiveness of the module, the researcher conducted a post-test in class on 10 students with an achievement percentage of 91.8% and very good qualifications. This shows that the use of the big book has met the criteria of being attractive and valid. Data analysis used the Paired Samples T Test with SPSS 16 tools, and the results were Sig 0.000 < 0.02, so Ho was rejected, meaning that there were differences in learning outcomes between students who had used the big book. So it can be concluded that the use of big books is able to improve literacy skills based on the Pancasila student profile..